Audio signal processing, MP3 encoder - Tan, Kian Siang (2016)
MP3 player, a device that can playback music but with a limited storage to store high quality music as its file size are larger. Usually the highest bitrate for MP3 is 320kbps but this results in larger file size. A method to reduce the file size is to lower the bitrate and the bitrate of 128kbps is the standard in mp3. Although the bitrate rate is much lower, it still maintained a good audio fidelity (Check the reference for the demo) [1]. This method is MP3 encoder, which it reduces the redundant data such as high frequency which cannot be perceived by our human ear and the lower frequency masked by higher frequency. Through the subband analysis filter bank, we can see there is data loss as the audio signal being split into 32 subband. Due to the audio signal being split into 32 subband, this introduced alias or noise artifact. By using the low pass prototype filter to window the input vector which stored the audio data, it can help to reduce the alias a little bit and the windowed data will be pass over to the 32x64 matrix and finally computing 18 subband samples. This resulted in reduced audio data value and hence why MP3 is a lossy compression.